2019
DOI: 10.2478/rmzmag-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemistry and petrogenesis of the Precambrian Basement Complex rocks around Akungba-Akoko, southwestern Nigeria

Abstract: Field, mineralogical and petrochemical studies of the Precambrian Basement Complex rocks around Akungba-Akoko were carried out with the aim of determining their petrology, petrochemical characteristics and petrogenesis. The petrology of Akungba-Akoko area comprises migmatite, granite gneiss and biotite gneiss intruded by biotite granite, charnockite and minor felsic and basic rocks. Seventeen representative samples of the granite gneiss, biotite gneiss, biotite granite and charnockite were collected during fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…This rock had undergone a series of tectonic deformations, which created both simple and complex structures comprising of folds, fractures and sheared zones. Since this granite gneiss is similar in forms, textures and colours to that found around Akungba-Akoko, it is likely that it has a similar chemical composition as reported in (Ogunyele et al 2019).…”
Section: Location and Geological Settingsupporting
confidence: 61%
See 1 more Smart Citation
“…This rock had undergone a series of tectonic deformations, which created both simple and complex structures comprising of folds, fractures and sheared zones. Since this granite gneiss is similar in forms, textures and colours to that found around Akungba-Akoko, it is likely that it has a similar chemical composition as reported in (Ogunyele et al 2019).…”
Section: Location and Geological Settingsupporting
confidence: 61%
“…Precambrian Basement Complex of Nigeria is located within the Pan-African Trans-Saharan mobile belt between the West African and Congo Cratons and to the south of the Tuareg Shield (Woakes et al 1987;Kroner et al 2001 Etioro-Akoko with its environs is underlain by the Migmatite-Gneiss Complex of the Precambrian Basement rocks of southwestern Nigeria. The granite gneissic rock is the predominant lithological unit in the study area as observed from detailed field geological mapping, and it is shown in Figure 3 (geological map of Etioro-Akoko combined with the geological map of Akungba-Akoko in the work of Ogunyele et al 2019). The granite gneiss of Etioro-Akoko, which extends to other parts of Akungba-Akoko area is weakly to moderately foliated, light grey, medium to coarse-grained in nature, with a blastoporphyritic to porphyroblastic fabric based on field observation.…”
Section: Location and Geological Settingmentioning
confidence: 93%
“…Other tarred and untarred roads found around connect one quarter to another, thus providing good accessibility to most parts of the area. The town is underlain by Precambrian Basement rocks of the southwestern Nigeria with migmatites and gneiss constituting the two dominant rock types [20] and [21] in Figure 3. The rocks outcrop as lowland and domy ridges trending E-W.…”
Section: Description Of the Study Environmentmentioning
confidence: 99%
“…The Southwestern Basement Complex of Nigeria comprises three major rock suites, namely the Migmatite-Gneiss Complex, the Schist belt, and the Older Granitoid. The Migmatite-Gneiss Complex rocks range in age from Neoproterozoic to Paleoproterozoic and Archean [20,21,22]; the Neoproterozoic Schist Belts, consisting of low-grade, younger metasedimentary, and metavolcanic rocks with ages ranging between 690 and 489 Ma [21,24,25], and the Pan-African Older Granites, which intruded the two earlier lithologies, have ages ranging between 650 and 580 Ma [25,26,27,28].…”
Section: Location and Geological Setting Of The Study Areamentioning
confidence: 99%
“…The Migmatite-Gneiss Complex rocks in the area are typically [31]). (c) Geological map of Akungba-Akoko and its surroundings in Ondo State, southwestern Nigeria, modified after [27]. migmatite, granite gneiss, biotite gneiss, and granitoids (charnockite and granite).…”
Section: Location and Geological Setting Of The Study Areamentioning
confidence: 99%